Management of Prostate Cancer A Multidisciplinary Approach - Bolla, Michel; Poppel, Hendrik; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book provides an exhaustive review of the current state of the art in the management of prostate cancer, from screening to treatment. A particular feature is the emphasis placed on the value of a multidisciplinary approach. The opening chapters address basic aspects including epidemiology, biology, and chemoprevention. The role of individual and mass screening is carefully appraised, and diagnosis, clinical work-up, and the role of active surveillance are discussed in detail. Subsequent chapters are devoted to each of the therapies that may be employed, including open and robotic laparoscopic radical prostatectomy, the various forms of radiation therapy, high-intensity focused ultrasound, cryotherapy, hormonal therapy, and targeted therapies and vaccination. Up-to-date data from clinical trials are included. In addition, the EAU guidelines are presented and advice is given on the interpretation of results. The authors are all experts in their field, and the editors are members of the EORTC who have coordinated phase III EORTC trials and have worldwide reputations.
Keywords: Medicine; Oncology; Radiotherapy; Epidemiology; Medicine & Public Health; Oncology; Radiotherapy; Epidemiology; Cancer Research